The industrial design aesthetic and its relationship with the recipient: باسم قاسم الغبان، صلاح نوري الجيلاوي (Al-Academy, 2015)
The research problem lies in determining the beauty ranges between the receiver and the industrial product, The goal of the research, it is the definition of aesthetics in industrial design and its relation to the receiver, and the researcher outcome several conclusions of the, the most important was: 1. The role of accumulated experience, and their interaction with the vision of the artwork in achieving aesthetic perception and levels of artistic and aesthetic values and by the level of growth this taste of the recipient. 2. There are interactive and close relationship be the primary means for the integration of functional and aesthetic meaning the designer meant to get it to the receiver.